Long-term outcomes in Primary congenital glaucoma, aniridia and anterior segment dysgenesis. Issue 5 (September 2022) - Magan, Tejal; Tanner, Alexander; Fajardo-Sanchez, Julia; Lim, Kin Sheng; Goyal, Saurabh; Rodrigues, Ian; Amaya, Luis; Trikha, Sameer; Kulkarni, Avinash; Hammond, Christopher; Lascaratos, Gerassimos; Yu-Wai-Man, Cynthia
Aim: To determine the long-term outcomes of a cohort of complex patients with primary congenital glaucoma, aniridia and anterior segment dysgenesis. Methods: Retrospective consecutive series between 1990–2021 in two UK tertiary centres: Guy's and St Thomas' NHS Foundation Trust and King's College Hospital NHS Foundation Trust. We recorded the number and types of surgical and laser treatments along with preoperative and postoperative data, including intraocular pressures (IOP) and anti-glaucoma medications. Results: A total of 41 eyes of 21 patients were included. Primary diagnoses were primary congenital glaucoma in 16 eyes (39.0%), aniridia in 14 eyes (34.2%), and anterior segment dysgenesis in 8 eyes (19.5%). Sixteen eyes (39.0%) had one or more glaucoma surgery or laser procedures for advanced glaucoma, and the long-term follow-up was 12.8 ± 3.6 years. There was a significant decrease in postoperative IOP (mmHg) at 3 months (16.5 ± 1.6; p = 0.0067), 6 months (18.7 ± 2.1; p = 0.0386), 12 months (18.6 ± 1.7; p = 0.0229), 3 years (14.7 ± 1.2; p = 0.0126), 5 years (15.5 ± 1.8; p = 0.0330) and 10 years (15.4 ± 2.3; p = 0.7780), compared to preoperatively (24.1 ± 2.6). Surgical success (complete and qualified) was 62.5%, 50.0%, 43.8%, 46.2%, 45.5% and 28.6% at 3 months, 6 months, 12 months, 3 years, 5 years and 10 years, respectively. There was no significant change in the number of anti-glaucoma drugs postoperatively ( p > 0.05). Four eyes (25.0%) had postoperative complications (hyphaema, hypotony) that resolved after conservative management. Conclusions: Surgical management of these complex eyes with advanced glaucoma is challenging. Overall, the cohort had good surgical outcomes with a significant decrease in IOP by 36.1% after long-term follow-up.